PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI PENDEKATAN CRT BERBANTUAN MODEL STAD PADA MATERI GARIS DAN SUDUT - Mahmudi; Ranila, Rahayu; Setyadi, Danang (Universitas Muhammadiyah Metro, 2024)
EEducation is a planned and conscious process aimed at guiding students to optimally develop their physical and spiritual potentials. In this context, mathematics education plays a crucial role in shaping students' critical and creative thinking abilities. However, many students struggle with and dislike mathematics, as observed at SMP Negeri 2 Salatiga. This study aims to improve students' mathematics learning outcomes by applying the Culturally Responsive Teaching (CRT) approach supported by the Student Teams Achievement Divisions (STAD) cooperative learning model on the topic of lines and angles. This Classroom Action Research (CAR) utilized the Kemmis and Taggart model, consisting of two action cycles. Data were collected through observation, tests, and documentation, and analyzed descriptively. The results showed a significant increase in the average mathematics scores from 55.85 in the pre-cycle to 70.42 in the first cycle, and 80.78 in the second cycle. Student activities also improved from